FACTORS AFFECTING SALT FARMER RESPONSE WAREHOUSE RECEIPT SYSTEM IN RACI VILLAGE BATANGAN DISTRICT - Sari, Anggun Novita; Yuliawati, Yuliawati (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.13, No.1, 2019DO - 10.24843/SOCA.2019.v13.i01.p01, 2019)
This study aims to describe the flow of implementation of the Warehouse Receipt System and find out the factors that influence the response of salt farmers to the Warehouse Receipt System. This research was conducted from June to July 2018 in Raci Village, Batangan district. Raci Village was chosen purposively as the location of the study taking into account that the storage location was inaugurated using Warehouse Receipt System. The sampling technique used was probability sampling with simple random sampling method and 70 respondents were taken. The data source used was primary data obtained from questionnaires and secondary data obtained from related institution such as BPS and Mutiara Laut Mandiri Coorperattive (MLM) as the warehouse manager. The data analysis techniques used is multiple linear regression using EViews 9.0 software. The result of the study shows that in Raci Village there was only one salt farmer that utilizes the Warehouse Receipt System and the factors that influence of salt farmers to the Warehouse Receipt System are the level of education, perception, and role field agricultural extension while the factors that did not influence were age, land area, and motivation.